Encyclopædia of religion and ethics - Hastings, James; Selbie, John A.; Gray, Louis H. (T. & T. Clark, 1908)
v. 1. A-Art.--v. 2. Arthur-Bunyan.--v. 3. Burial-Confessions.--v. 4. Confirmation-Drama.--v. 5. Dravidians-Fichte.--v. 6. Fiction-Hyksos.--v. 7. Hymms-Liberty.--v. 8. Life and death-Mulla.--v. 9. Mundas-Phrygians.--v. 10. Picts-Sacraments.--v. 11. Sacrifice-Sudra.--v. 12. Suffering-Zwingli.--v. 13. Indexes.